Family Control and Investment Efficiency: Does Financial Analyst Coverage Matter? - Jedda, Nour; Lakhal, Faten; Ghenima, Riadh (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
The purpose of this paper is to investigate the effect of family control on investment efficiency and to highlight the moderating effect of analyst coverage. Based on a sample of French-listed companies, the results show a negative effect of family excess control and successive generational stage on investment efficiency. This negative effect is mainly driven by the underinvestment problem. These findings suggest that family firms are associated with exacerbated information asymmetry issues leading them to miss investment opportunities. However, analyst coverage, as an external corporate governance device, helps mitigating information asymmetry and the problem of inefficient investments in family firms.